Melanoma metastasis mimicking gastric cancer: a challenge that starts from diagnosis. (February 2021) - Monti, Manlio; Guidoboni, Massimo; Oboldi, Devil; Bartolini, Giulia; Pieri, Federica; Ruscelli, Silvia; Passardi, Alessandro; Ridolfi, Laura; De Rosa, Francesco; Sullo, Francesco Giulio; Frassineti, Giovanni Luca
The gastrointestinal tract is an uncommon site of metastasis in melanoma. However, when the primary melanoma cannot be found, the diagnosis of gastric melanoma by endoscopic biopsy is problematic mainly because some tumors are amelanotic and do not contain melanin granules detectable by microscopy. A 56-year-old Caucasian man with melanoma was referred to us following an initial histopathological diagnosis via gastroscopy of poorly differentiated primary gastric carcinoma. A computerized tomography (CT) scan showed metastatic disease and on the basis of this information we started palliative chemotherapy. However, the atypical presentation of the disease with subcutaneous metastases prompted us to make a more in-depth evaluation. Immunohistochemical evaluation modified the diagnosis to melanoma. After only one cycle of chemotherapy, treatment was changed to dabrafenib + trametinib, which was better tolerated and initially induced a partial response. The patient is currently in good clinical condition 20 months after diagnosis. Our case report highlights the difficulty in diagnosing melanoma of the gastrointestinal tract and indicates the need for pathologists and clinicians to consider such a possibility when they are faced with a diagnosis of poorly differentiated gastric cancer and unusual sites of metastasis.